The Contribution of SIAKAD to Academic Information Transparency for IAIN Ternate Students - Aril Rahnul Samman; Minggusta Juliadarma; Adiyana Adam (Manunggal Halim Jaya, 2026)
Transparency of academic information is an important indicator of good university governance. The utilization of the Academic Information System (SIAKAD) is expected to support academic information openness for students effectively and sustainably. This study aims to analyze SIAKAD’s contribution to the transparency of academic information for students at IAIN Ternate. This study used a quantitative approach with a correlational descriptive design. Data were collected through closed questionnaires using a Likert scale for active SIAKAD users and then analyzed using descriptive statistics and simple regression analysis. The results of the study show that the utilization of SIAKAD falls into the good category, with online KRS entry, grade access, and class schedule information being the most frequently used services. The regression analysis results indicate that SIAKAD has a positive and significant effect on transparency in academic information. This finding suggests that the more optimally SIAKAD is utilized, the higher the level of academic information transparency that students perceive. However, delays in data updates and inconsistencies in information input remain issues that require attention. This study recommends improving the quality of SIAKAD management and strengthening the commitment of all academic components to achieve optimal academic information transparency.